How To Build A Great Knowledge Management Portal - Hariharan, Arun (Journal of Knowledge Management Practice, 2011)
Technology can be a powerful enabler to make Knowledge Management (KM) effective and to maximize its results. The most commonly used technology-support for KM is the KM portal that often forms part of a company’s Intranet. However, examples of companies that sunk tons of money in sophisticated technology solutions for KM without any real business results abound. This article begins with real examples of companies that have derived significant business results through their KM program, of which their KM portal is a key enabler. It then talks about how to keep the KM portal simple for the user. Next, we look at how your KM portal can enable 360-degree KM. Finally, it provides a list of functionality and features that a KM portal must provide in order to be a serious enabler of better business performance. The article is based on first-hand experience with world-class KM systems and practices at a global professional services firm, followed by leading the conceptualization and implementation of KM systems at several large and different businesses that derived breakthrough results through KM, and a study of KM portals at other organizations.
Keywords: Knowledge management; KM portals; KM technology; KM solutions